Tata Kelola Media Sosial Bagi Penguatan Akuntabilitas Dana Desa di Desa Surianeun, Kabupaten Pandeglang - Bambang Arianto (Rahmatan Lil 'Alamin Journal of Community Services, 2023)
The demand for public accountability in the management of village funds means that social media can be used as an alternative means. Social media can be useful in informing various Village Government programs and village fund management. In community service in Surianeun Village, Pandeglang Regency which was held on 15th February 2023, social media management assistance was provided as a means of public accountability in managing village funds. In this assistance, material on social media management and creative content creation has been provided. From the results of this activity it is known that social media governance assistance has enabled government officials in Surianeun Village to utilize social media as a means of public accountability in managing village funds. The success of this activity can be seen from Village Government officials who can create creative content and improve social media governance. Furthermore, the Surianeun Village government officials understand the usefulness of social media as a means of public accountability in the management of village funds in Pandeglang Regency.